Microbiological assessment of fish kinilaw from tanguigue (Scomberomorus commerson) - Cruz , Aida Rizza Zaragoza (Sotech, 2003)
Local vinegar from tuba and commercial (Del Monte Red Cane) vinegar were used separately in preparing fish kinilaw.